Distribution pattern of benthos based on substrate in the mangrove area of Labuhan Haji District, South Aceh Regency - Rasma Hasyiati; Muhammad Ali Sarong; Safrida Safrida; Djufri Djufri; Ismul Huda (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Mangrove areas can function as habitats for spawning, rearing, and foraging for various species in them. Benthos is an organism that lives on the bottom of the water. Research on benthos distribution patterns based on substrate was carried out with the aim of studying benthos species, types of substrates, and analyzing benthos distribution patterns based on substrates in Labuhan Haji District, South Aceh District, Aceh Province. The method used in this study is the method of observation and field work. The benthos distribution pattern based on the substrate was calculated using the morphic index. Identification results found 31 species of benthos consisting of 3 classes, namely gastropods with 7 orders, bivalves with 4 orders, and malacostraca with 1 order and the type of substrate analyzed obtained 4 types of substrate namely dusty loam, sandy loam, silt and sand. The benthos distribution pattern based on the substrate obtained 2 categories, namely uniform on sandy loam and sandy clay substrates, and clustered on dusty and dusty clay substrates.Keywords:MangrovesBenthosSubstrate TypeSpread patternLabuhan Haji